Variation and Trends in Charges for Pediatric Care in Massachusetts Emergency Departments, 2000–2011. (22nd September 2015) - Monuteaux, Michael C.; Bourgeois, Florence T.; Mannix, Rebekah; Samnaliev, Mihail; Stack, Anne M.; Pines, Jesse
Abstract Objectives Emergency department (ED) utilization by children is common and growing more expensive. Tracking trends and variability in ED charges is essential for policymakers who strive to improve the efficiency of the health care system and for payers who prepare health care budget forecasts. Our objective was to examine trends and variability in ED charges for pediatric patients across Massachusetts. Methods This was a comprehensive analysis of the statewide database containing all the visits of children aged 0 to 18 years evaluated in any of the state's EDs from 2000 to 2011, excluding patients with chronic medical conditions and those whose visits resulted in hospital admission. A validated system designed to specifically classify pediatric emergency patients into major diagnostic groups was used. Mean charges as well as interhospital variability of charges over time were examined for the most common diagnostic groups. Results Seventy‐six hospitals provided emergency care in Massachusetts during the study period, with 6, 249, 923 pediatric patients treated and discharged. Statewide charges significantly increased from 2000 until 2007/2008, before plateauing or decreasing through 2011. There was no evidence that interhospital variability changed over time. With the exception of academic teaching status, no hospital‐level factors emerged as consistent predictors of charges. Conclusions Charges for common pediatric emergency conditions varied widely across Massachusetts EDs, and hospital‐level factors by and large could not consistently explain the variability. Although a plateau (and in some cases decrease) of statewide pediatric emergency health care charges was observed after 2007, no evidence was found that interhospital variability decreased. These data may be useful in the ongoing effort to reform the economics of health care delivery systems.